Assessment for Learning: Meeting the Challenge of Implementation [electronic resource] - Laveault, Dany.; Allal, Linda; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides new perspectives on Assessment for Learning (AfL), on the challenges encountered in its implementation, and on the diverse ways of meeting these challenges. It brings together contributions from authors working in a wide range of educational contexts: Australia, Canada, England, Germany, New Zealand, Norway, Israel, Philippines, Scotland, Spain, Sweden, Switzerland, the United States. It reflects the issues, innovations, and critical reflections that are emerging in an expanding international network of researchers, professional development providers, and policy makers, all of whom work closely with classroom teachers and school leaders to improve the assessment of student learning.{u0528}e concept of Assessment for Learning, initially formulated in 1999 by the Assessment Reform Group in the United Kingdom, has inspired new ways of conceiving and practicing classroom assessment in education systems around the world. This book examines assessment for learning in a broad perspective which includes diverse approaches to formative assessment (some emphasizing teacher intervention, others student involvement in assessment), as well as some forms of summative assessment designed to support student learning. The focus is on assessment in K-12 classrooms and on the continuing professional learning of teachers and school leaders working with these classrooms.{u04A5}aders of this volume will encounter well documented accounts of AfL implementation across a large spectrum of conditions in different countries and thereby acquire better understanding of the challenges that emerge in the transition from theory and policy to classroom practice. They will also discover a wealth of ideas for implementing assessment for learning in an effective and sustainable manner.{u4A25} chapters are grouped in three Parts: (1) Assessment Policy Enactment in Education Systems; (2) Professional Development and Collaborative Learning about Assessment; (3) Assessment Culture and the Co-Regulation of Learning. An introduction to each Part provides an overview and presents the suggestions and recommendations formulated in the chapters.{uE035}
1. Implementing Assessment for Learning: Theoretical and Practical Issues -- PART I: Assessment Policy Enactment in Education Systems -- 2. Assessment Policy Enactment in Education Systems: A Few Reasons to Be Optimistic -- 3. Making Meaning of Assessment Policy in Australia through Teacher Assessment Conversations -- 4. Effective Enactment of Assessment for Learning and Student Diversity in Australia -- 5. Formative Assessment Policy and its Enactment in the Philippines -- 6. Communication and Collaboration: The Heart of Coherent Policy and Practice in New Zealand Assessment -- 7. More than Good Intentions: Policy and Assessment for Learning in Scotland -- PART II: Professional Development and Collaborative Learning about Assessment -- 8. Building Capacity: Professional Development and Collaborative Learning about Assessment -- 9. Implementing Assessment for Learning in Canada: The Challenge of Teacher Professional Development -- 10. Teachers? Professional Development in the Context of Collaborative Research: Toward Practices of Collaborative Assessment for Learning in the Classroom -- 11. Cooperative Learning about Assessment for Learning -- 12. Developing Assessment for Learning Practice in a School Cluster: Primary and Secondary Teachers Learning Together -- 13. Implementing High Quality Assessment for Learning: Mapping as a Professional Development Tool for Understanding the What to Learn, Why to Learn It, and How to Learn It -- 14. Assessment for Learning: A Framework for Educators' Professional Growth and Evaluation Cycles -- PART III: Assessment Culture and the Co-Regulation of Learning -- 15. The Co-Regulation of Student Learning in an Assessment for Learning Culture -- 16. Assessment Culture vs. Testing Culture: The Impact on Assessment for Learning -- 17. The Role of Classroom Assessment in Supporting Self-Regulated Learning.-{u1E2E} Scaffolding Self-Regulated Learning through Self-Assessment and Peer Assessment: Guidelines for Classroom Implementation -- 19. Assessment for Learning: Co-Regulation In and As Student-Teacher Interaction -- 20. Supporting Students? Learning: From Teacher Regulation to Co-Regulation. {uE000}
Keywords: Education; School management and organization; School administration; Educational policy; ducation and state; Assessment; Education; Assessment, Testing and Evaluation; Educational Policy and Politics; Administration, Organization and Leadership